ANALISIS KEBUTUHAN KAWASAN HUTAN KOTA BERDASARKAN EMISI KARBON DIOKSIDADI KOTA PIRU, SERAM BAGIAN BARAT - Sartje Untajana; Robert Oszaer; Yosevita Th. Latupapua (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
The objective of the study is to determine urban forest area, based on carbon dioxyde emission estimation from vehicle traffic and human activities in the city and around. The result of carbon dioxyde emission calculation used as a basic to determine proportional forest area to established. The comprhensive plan of urban forest, covers species and vegetation type that projected to be able to abrsorb the emission. The analysis shows that amount of carbon dioxyde emission from vehicle traffic in the city was 50,186.4 tons/year, meanwhile, carbon dioxyde produced by human respiratory activities was 9,499.47 ton/year. The necessary of urban forest area to absorb the amount of that emission is 12.67 hectare. Calculation of vegetation space approximately 10 x 10 m2, based on assumption that to absorb carbon dioxyde is in the central of city. Therefore to be recommended that the type of the urban forest is recreation forest type, in order to improve aestetic and convenience of the city in the future. The number of species to be planted is consists of 21 species, which 30 % of the forest area will designed as an open space area for community interaction. Therefore, the number of trees to be planted is about 620.56 individu of tree.